UPAYA GURU DALAM MENINGKATKAN AKTIVITAS BELAJAR PADA PEMBELAJARAN TEMATIK SISWA DI MASA PANDEMI COVID-19 KELAS V SD IES AL-GHUROBA KABUPATEN SORONG - Erwinestri Hanidar Nur Afifi; Fatimatus Zahro (MISOOL: Jurnal Pendidikan Dasar, 2021)
This thesis discusses the Teacher's Efforts in Improving Activities Learning on thematic Learning for Students during the Covid-19 Pandemic Class V Elementary School IES Al-Ghuroba' Sorong Regency. Researchers focus research on 1). The teacher's efforts in improving learning activities in thematic learning during the Covid-19 pandemic, class V students. 2). Teacher supporting factors in increase activities in thematic learning during the covid-19 pandemic. 3). Factors inhibiting teachers in increasing activities in thematic learning during the covid-19 pandemic. This research uses qualitative research, subject in this study were principals, fifth-grade teachers, fifth-grade students data collection using observation, interviews, and documentation. The results of this study are for face-to-face learning, efforts from the teacher to increase student activity in learning, namely establishing a short but effective learning time. Prepare learning in various methods is integrated into the game. And for learning online this is done via video. Inhibiting factors in increasing student learning activities are limited study time for all activities learn in thematic learning and other learning, as well as parents who do not have supporting media for learning, namely Hand Phone (HP). Factor Supporters in increasing student learning activities are teachers preparing creative learning that is supported by the media and starts with the preparation of lesson plans, the role of parents, the cooperation of parents and teachers